Investigating the Dynamic Return Spillover Effect amidst Selected large Stock Exchange Companies: New Evidence from the Contemporaneous and Lagged R2 Connectedness Approach - Sara Komasi; Ezatollah Abbasian (راهبرد مدیریت مالی)
Investment portfolio management is always one of the concerns of investors. Therefore, in this research, the net transmitter or receiver of volatilities amidst the selected large companies in the period of 08/10/2015-04/29/2024 using the vector autoregressive model with time-varying parameters and the R2 connectedness that was developed by Balli et al. (2023) has been investigated. The results showed that in contemporaneous status and daily trading policy, Foulad had the most net effect on other components of the portfolio and Mellat Bank had the most net effect on other components of the network. Also, Behran was the biggest net transmitter and Femeli was the most net receiver in the contemporaneous mode and in the investigated network. In the bullish mode, there is no relationship between the stocks in the portfolio. In the conditions of balanced growth of stocks, in general, and overall, Behran has transferred its volatility and risk to Femeli, and no correlation has been seen among other stocks. Based on this, portfolio management should be considered depending on the states of contemporaneous, lagged, and bullish or bearish stock market.